2021
DOI: 10.1007/s11356-021-15154-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glacier status and its controlling parameters from 1990 to 2018 of Hunza Basin, Western Karakorum

Abstract: Ice masses and snow of Hunza River Basin (HRB) are an important primary source of fresh water and lifeline for downstream inhabitants. Changing climatic conditions seriously put an impact on these available ice and snow masses. These glaciers may affect downstream population by glacial lake outburst oods (GLOF) and surge events due to climatic variation. So, monitoring of these glaciers and available ice masses are important. This research delivers an approach for selected glaciers of the Hunza river basin. An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Fowler and Archer, (2006) stated that the summer season's temperature plays a key role in SCA and glacier melt; another study also stated that the pre-monsoon and monsoon temperature of the high mountain area is decreasing (Hussain et al, 2005). The elevation and SCA were also analyzed, and it was found that zone 1 of both regions has a decreasing trend (Qureshi et al, 2017;Ali et al, 2021), while zone 4 has a slightly increasing trend of SCA because the high-altitude region is less exposed to solar radiation as compared to foothills (Saydi and Ding, 2020). The higher altitude regions have consistently below-freezing temperatures throughout the year; therefore, increasing precipitation can possibly feed the high-altitude region, and hence SCA expands (Tahir et al, 2011;Hasson et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Fowler and Archer, (2006) stated that the summer season's temperature plays a key role in SCA and glacier melt; another study also stated that the pre-monsoon and monsoon temperature of the high mountain area is decreasing (Hussain et al, 2005). The elevation and SCA were also analyzed, and it was found that zone 1 of both regions has a decreasing trend (Qureshi et al, 2017;Ali et al, 2021), while zone 4 has a slightly increasing trend of SCA because the high-altitude region is less exposed to solar radiation as compared to foothills (Saydi and Ding, 2020). The higher altitude regions have consistently below-freezing temperatures throughout the year; therefore, increasing precipitation can possibly feed the high-altitude region, and hence SCA expands (Tahir et al, 2011;Hasson et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The eastern Karakoram (i.e., Shyok sub-basin) receives water input mainly from the summer monsoon while, in the western Karakoram (i.e., Hunza and Shigar sub-basins), precipitation comes mainly during winter and spring via the winter westerly disturbances (WWD; Dahri et al, 2016Dahri et al, , 2018Hasson et al, 2014;Hewitt, 2011;Rees and Collins, 2006). In recent decades, there has been an increasing trend in precipitation amounts observed over the western Karakoram (Ali et al, 2021).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…One of the notable impacts of climate change in the Himalaya is the signi cant glacier thinning and melting (Shrestha and Aryal 2011;Ali et al 2021;Dixit et al 2021). However, the observed thinning and melting is characterized by heterogeneity across the Himalaya (Abdullah et al 2020;Sakai and Fujita 2017;Farinotti et al 2020).…”
Section: Introductionmentioning
confidence: 99%